LEGAL PERSPECTIVES ON DATA PRIVACY AND CYBERSECURITY IN THE DIGITAL AGE - Indah Susilowati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This article examines the evolving legal frameworks governing data privacy and cybersecurity in the contemporary digital landscape. As technological advancements continue to reshape how personal data is collected, processed, and utilized, legal systems worldwide are confronted with unprecedented challenges in balancing innovation with individual rights protection. Through comparative analysis of major jurisdictional approaches including the European Union's General Data Protection Regulation (GDPR), the California Consumer Privacy Act (CCPA), and emerging regulatory frameworks in Asia-Pacific regions, this study identifies key convergence points and divergences in global data protection regimes. The research further explores the legal implications of emerging technologies such as artificial intelligence, biometrics, and the Internet of Things (IoT) on privacy and security paradigms. Findings indicate that while regulatory fragmentation remains a significant challenge, there is growing international consensus around core principles of transparency, consent, data minimization, and security by design. The article concludes by proposing a harmonized approach to data privacy and cybersecurity regulation that accommodates technological innovation while ensuring robust protection of fundamental rights in the digital age.